Periodical prestige and criminal justice: An assessment of professional journals [1] - Poole, Eric D. (American journal of criminal justice, 1983)
It is a seemingly easy task to generate periodical rankings for an academic discipline. Yet, upon closer inspection, the validity of this claim is questionable, particularly for disciplines lacking a well-defined membership or scholarship boundaries. Criminal justice is one such discipline. Data for the project were derived from questionnaire responses of 1,028 persons who were members of the Academy of Criminal Justice Sciences, American Sociey of Criminology, or both associations, via a three-wave mail survey in September 1979. The study’s most interesing findings were: (1) noncriminologists assigned periodicals a wider range of weights than criminologists; (2) periodical publishers assigned higher weights than nonpublishers; (3) periodical rankings were most similar among published and nonpublished noncriminologists; and (4) respondents generally agreed on what constitutes the poorer journals.